Undergraduate Student Perspectives on Employability: A Mixed Methods Exploration of Nutrition Student Career Awareness, Confidence, and Preparedness - Ashley Ng; Anj Reddy; Deanna Horvath; Amy Larsen; Jessica Biesiekierski; Sharon Croxford; Andrea Bramley; Susan McLeod; Emma Stirling; Emily Murray; Adrienne Forsyth (Journal of Teaching and Learning for Graduate Employability, 2023)
There is a growing need for nutrition graduates to fill diverse roles that will address emerging health priorities including community-based chronic disease prevention, personalised nutrition, digital health, and innovations in food and agriculture. Little is known about how well universities are preparing nutrition students to fill these roles. The aim of this study was to explore undergraduate nutrition students’ career awareness, confidence, and preparedness. A secondary aim was to explore their perspectives regarding employability initiatives within the university curriculum. A mixed methods approach was used, including semi-structured focus groups to gain in-depth insights and surveys to expand and diversify the study population, enhancing validity and transferability of the findings. Results of the focus groups were analysed thematically using an inductive approach. Initial themes informed the survey with closed questions analysed using descriptive statistics and open questions analysed thematically. Seven students participated in focus groups and 73 completed the survey. Common themes arising from the focus group and survey responses included a lack of awareness of roles available to nutritionists, lack of placement experience seen as a link to understanding what nutritionists do and getting that first job, and life experiences and personal circumstances influencing career pathways. Practical opportunities for nutrition students to develop their career awareness, confidence, and preparedness should be a key consideration in the design of the undergraduate nutrition curricula.